ANALISIS KONSEPTUAL PEMILIHAN SUBJEK RISET, POPULASI, DAN SAMPEL DALAM PENELITIAN PENDIDIKAN DASAR - Fauzil Ihya Husaini; Nuril Huda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the still-limited conceptual understanding among researchers, particularly in the field of elementary education, regarding the proper selection of research subjects, populations, and samples, which compromises the validity and accuracy of research findings. The purpose of this study is to conduct a conceptual review of the selection of research subjects, populations, and samples in elementary education research. The method used is a literature review by examining various relevant sources, such as books and previous research findings. Data analysis was conducted using content analysis techniques to produce wellorganized and accountable conclusions. The research findings indicate that the research subject, population, and sample are fundamental, interrelated components in the research process. The research subject serves as the primary data source; the population consists of all units of analysis sharing specific characteristics; while the sample is a representative portion of the population. Errors in determining these three components can introduce research bias and reduce the validity of research results. Thus, a strong grasp of these concepts and careful selection of the research subject, population, and sample are essential to produce research that is valid, reliable, and scientifically accountable, particularly in basic education research.